Patient with End-Stage Renal Disease (ESRD) Experienced a Malfunction of Continuous Ambulatory Peritoneal Dialysis (CAPD) Accompanied by Central Venous Stenosis (CVS) Complications: A Case Study - Mochammad Dilliawan , Satriyo Dwi Suryantoro (South Eastern European Journal of Public Health, 2025)
Peritoneal dialysis (PD) is a reliable treatment for end-stage renal disease (ESRD) users, accounting for around 8% of the chronic kidney disease (CKD) patient population globally. It can be done at home and is not prone to outflow disorders caused by infections. Common causes include constipation, kinked catheters, intraluminal catheter debris, and omental wrap. Technical failures are common during PD, with 18 out of 45 patients undergoing CAPD having non-infectious complications. Central venous stenosis (CVS) is a vascular access problem in CKD patients, with an incidence of 4.1-4.3%. we present a case of a 52-year-old man with abdominal pain, swollen hands and legs, and decreased appetite reported to the emergency department. The patient's CAPD drainage decreased and the patient's blood sugar level was low, requiring hospitalization. The CAPD process appears stagnant. The findings show that the patient experienced a CAPD malfunction due to catheter lumen plugging and central venous stenosis, requiring laparoscopic plugging evacuation and omentectomy. Other medical issues included stroke, anemia, hypoalbuminemia, and hypokalemia, which were managed during hospitalization. Post-repair CAPD response was good.